PROFILE OF LYCOPENE UV-SPECTRA OF LACTIC ACID BACTERIA FERMENTED MILK-TOMATO PASTE - Isnaeni Isnaeni; Nailatul Hidayah; Utari Ardiningdyah; Izza Rahmi Hidayah (Sanata Dharma University, 2019)
Lycopene is one of the famous ingredients in tomatoes, because of its important role as a potent anti-oxidant. Besides being consumed as fresh fruit, tomato paste can be combined with probiotic fermented milk to increase its health benefits. Probiotics are lactic acid bacteria (LAB), which when consumed in sufficient quantities will benefit health. Probiotic fermented milk is reported to have various properties including anti-microbial, antioxidant, immunomodulatory and anti-cancer, so the combination with tomato paste is expected to increase its benefits for health. This research aimed to study the effect of probiotic fermented milk on the content of tomato paste lycopene. Lactobacillus acidophillus, Lactobacillus bulgaricus, and Lactobacillus casei were used as mixed probiotic cultures. It was found that at the ratio of 2:8 for the LAB fermented milk and tomato paste, the highest lycopene drive was obtained by spectrophotometric measurement at 663, 645, 505, and 453 nm. Determination of the lycopene content was performed according to the Nagata and Yamashita simple methods. In addition, the lycopene content in the LAB fermented milk-tomato paste was greater than the content in the tomato paste without fermented milk addition and was tested stable after storage for 14 days.